Culture and Testing Practices: Is the World Flat?. Issue 3 (7th March 2017) - Ryan, Ann Marie; Reeder, Matthew C.; Golubovich, Juliya; Grand, James; Inceoglu, Ilke; Bartram, Dave; Derous, Eva; Nikolaou, Ioannis; Yao, Xiang
Abstract : There has been much speculation regarding the influence of cultural norms on the acceptance and use of personnel selection testing. This study examined the cross‐level direct effects of four societal cultural variables (performance orientation, future orientation, uncertainty avoidance, and tightness–looseness) on selection practices of organisations in 23 countries. A total of 1, 153 HR professionals responded to a survey regarding testing practices in hiring contexts. Overall, little evidence of a connection between cultural practices and selection practices emerged. Implications of these findings for personnel selection and cross‐cultural research as well as directions for future work in this area are described.